The effect of temperature, cyanide and base metals on the adsorption of Pt, Pd and Au onto activated carbon - Snyders, C.; Bradshaw, S.; Akdogan, G.; Eksteen, Jacques (Elsevier, 2014)
Leaching of platinum and palladium with alkaline cyanide solutions has been shown to be feasible for a number of leach modes. The platinum and palladium leaching will typically take place at elevated temperatures, which can range from 55 °C on heaps or in tanks to between 120 and 180 °C in autoclaves with a better degree of leaching occurring with higher temperatures. Some progress has also been made into the investigation of PGM (platinum group metals; Pt, Pd, Au) adsorption onto activated carbon at room temperature, but as typically higher temperatures (> 55 °C) are likely for the leaching of Pt and Pd, it is an important factor in the adsorption process of which the effect is still largely unknown. The effects of temperature, free cyanide and base metal (Cu and Ni) concentrations on the adsorption of PGMs from pregnant leach solutions onto granular activated carbon were therefore determined. Common to most diffusion controlled processes, an increase in the adsorption rate of platinum, palladium and gold cyanide with an increase in temperature was observed. Experiments with consecutive contacts of the PGM cyanide solution onto the activated carbon, however, revealed that with an increase in temperature, the amount of PGMs that were adsorbed, decreased with each loading. In the absence of free cyanide and base metals, it was found that after 4 consecutive contacts, 99% of the total amount of Pt and Pd adsorbed at 25 °C compared to 85% of the Pt and 83% of the Pd at 50 °C. No difference could be seen between the adsorption of gold cyanide at 25 and 50 °C after 4 contacts. It has also been established that the detrimental effect of free cyanide on the adsorption of PGMs will increase as the temperature increases. The detrimental effect of the presence of Cu and Ni is evaluated, based upon the amount of the base metals adsorbed at these conditions, which have been found to vary significantly with cyanide and temperature. Generally, Pt and Pd adsorption has been found to be significantly more affected by temperature, cyanide and base metals than the adsorption of gold and needs to be carefully taken into consideration with the design of a PGM adsorption circuit to ensure sufficient Pt and Pd recovery.